GEOESTATISTICS APPLIED TO SPATIAL DISTRIBUTION OF THE PRECIPITATION - Silvestre, Miriam Rodrigues [UNESP]; Flores, Edilson Ferreira [UNESP]; Sant'Anna Neto, Joao Lima [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2016)
The spatial distribution of certain climatic element from collected sample points is a usual task in Climatology. However, the phenomenon generally presents spatially correlated so that there is a need to use an interpolation method that considers the presence of correlation between observations. Geostatistics is a technique capable of incorporating the spatial correlation in its procedures, and therefore quite used in several areas. But not always the steps required in technical employment are followed by their users, making the maps produced without the care of their application can not be representations consistent with the actual representation of the phenomenon in space. Thus, this paper aims to present the theory of geostatistics technique and illustrate how an analysis should be performed following all the steps that the technique calls through two examples of application in rainfall data for the Parana branch of Paranapanema basin. The results are obtained through Variowin (R) 2.21 and ArcMap (R) 10.1 software, and evaluated by the statistical mean square error of the square root (RMSE).
Keywords: spatial interpolation; geostatistics; ordinary kriging; precipitation; climatology